Associations of sNfL with clinico‐radiological measures in a large MS population - Sotirchos, Elias S.; Fitzgerald, Kathryn C.; Singh, Carol M.; Smith, Matthew D.; Reyes‐Mantilla, Maria; Hersh, Carrie M.; Hyland, Megan H.; Canissario, Ryan; Simmons, Sarah B.; Arrambide, Georgina; Montalban, Xavier; Comabella, Manuel; et al. (Annals of clinical and translational neurology, 2023)
Objective Evaluation of serum neurofilament light chain (sNfL), measured using high‐throughput assays on widely accessible platforms in large, real‐world MS populations, is a critical step for sNfL to be utilized in clinical practice. Methods Multiple Sclerosis Partners Advancing Technology and Health Solutions (MS PATHS) is a network of healthcare institutions in the United States and Europe collecting standardized clinical/imaging data and biospecimens during routine clinic visits. sNfL was measured in 6974 MS and 201 healthy control (HC) participants, using a high‐throughput, scalable immunoassay. Results Elevated sNfL levels for age (sNfL‐E) were found in 1238 MS participants (17.8%). Factors associated with sNfL‐E included male sex, younger age, progressive disease subtype, diabetes mellitus, impaired renal function, and active smoking. Higher body mass index (BMI) was associated with lower odds of elevated sNfL. Active treatment with disease‐modifying therapy was associated with lower odds of sNfL‐E. MS participants with sNfL‐E exhibited worse neurological function (patient‐reported disability, walking speed, manual dexterity, and cognitive processing speed), lower brain parenchymal fraction, and higher T2 lesion volume. Longitudinal analyses revealed accelerated short‐term rates of whole brain atrophy in sNfL‐E participants and higher odds of new T2 lesion development, although both MS participants with or without sNfL‐E exhibited faster rates of whole brain atrophy compared to HC. Findings were consistent in analyses examining age‐normative sNfL Z‐scores as a continuous variable. Interpretation Elevated sNfL is associated with clinical disability, inflammatory disease activity, and whole brain atrophy in MS, but interpretation needs to account for comorbidities including impaired renal function, diabetes, and smoking.